Pengembangan Media Pembelajaran pada Materi Peninggalan Kerajaan Hindu-Buddha di Indonesia Berbasis Augmented Reality di Kelas IV SD - Dela Septiani Sesarianty; I Nyoman Indhi Wirandika; Luh Putu Eka Damayanthi (TIN: Terapan Informatika Nusantara, 2026)
Education in the modern era requires innovation in learning media to improve students' understanding of abstract material, especially on material from the Hindu-Buddhist Kingdom heritage in Indonesia, such as temples and inscriptions. This study aims to develop Augmented Reality (AR)-based learning media. The media is designed to overcome the limitations of conventional methods such as lectures and textbooks that are difficult to visualize. The research method uses Research and Development (R&D) with the Multimedia Development Life Cycle (MDLC) development model. The resulting products include the SejaRah application, AR Books, and AR Cards. Students can scan markers to display three-dimensional objects of temples and inscriptions, equipped with audio explanations and interactive quizzes. The subjects of this study were grade IV elementary school students. Testing of the SejaRah learning media has been carried out by conducting a black box test with 100% appropriate results, content and media expert validity with a score of 100% each with the category "Very valid, or can be used without revision", and user response testing using the User Experience Questionnaire (UEQ). The UEQ test results show the "Excellent" category in all aspects of the assessment. Thus, the learning media is declared valid and receives a positive user response so that it is suitable for use as a learning medium for the heritage of the Hindu-Buddhist kingdom in Indonesia for grade students. IV broadly.